Sentiment analysis based on deep learning - Jiang, Qi (Nanyang Technological University, 2021)
As millions of messages are posted and thousands of articles are published every day, a lot of information is stored in form of natural unstructured text. Natural Language Processing (NLP) aims to extract information from text and understand text using computational methods. One of the most important tasks of NLP is sentiment analysis, also known as opinion mining, which studies people’s opinions, sentiment polarities, emotions, and attitudes. Sentiment analysis is of great significance as it can be applied to and benefit a wide range of industries including business sales, governments, social media etc. It is a challenging task and has been studied for decades with various rule-based approaches and machine learning approaches.